The Importance of Employability Skills for Hospitality Graduates toward Employment Status - Muhammad Amil Hakim A. Ghani; Wan Hanis Syazwani Wan Talib; Wan Nazriah Wan Nawawi; Haslina Che Ngah; Yudhiet Fajar Dewantara (Information Management and Business Review, 2025)
Every individual strives to achieve their dream profession to lead a comfortable life. Currently, individuals are engaged in intense competition to secure employment, particularly those that offer superior perks and remuneration. In today's competitive job market, hospitality graduates need more than just technical knowledge to secure employment. The purpose of this research is to examine the elements that influence the identification of employable abilities as perceived by hospitality graduates. The research study investigates the importance of employability skills among hospitality graduates and their impact on employment status. The primary research problem addresses how soft and hard skills contribute to graduates' job market readiness. The research is quantitative, gathering data from participants through questionnaires. The total number of hospitality graduates involved in answering the questionnaire is 155 respondents. The data demonstrates that employability skills, both soft and hard, are crucial for securing job offers. Major findings indicate that graduates possessing a balanced combination of soft and hard skills have higher employment rates and better job performance. The outcome of this study is to show that employability skills, like hard and soft skills, are important for future careers after graduating from university.  This study can raise awareness among current students, particularly those in the hospitality field, about the importance of enhancing their skills beyond their university education.